Ресурсо- и энергосбережение при получении сырого бензола из коксового газа - Лаврова, Инна Олеговна; Лавров, О. И. (НТУ "ХПИ", 2006)
In article the basic requirements which are put forward by practice of carrying out of process absorption of Benzene hydrocarbons from coke gas and reception of crude benzene are considered. Last achievements in considered process are resulted, opportunities of substantial increase of economic parameters and optimum ways of their realization are shown.
Keywords: бензольные углеводороды; абсорбция; поглотительное масло